PENYELESAIAN HUKUM WANPRESTASI PERJANJIAN KERJA SAMA ANTARA PT. ERENHA LANGGENG KARSA DENGAN PT. TANAH UNTUK ANAK NEGERI (GURINDAM PROPERTY) TENTANG PEMASARAN PERUMAHAN GRAHA NUANSA DAMAI 4 - Majid, Sidratul Salsabilla; Raihana, Raihana; Rachman, Miftahur (LPPM, Universitas Muhammadiyah Riau, 2024)
Implementation of the agreement that is negligent in carrying out its achievements or obligations contained in the agreed cooperation agreement. In the cooperation agreement, a default occurs. The problem in this study is about the late payment of wages or fees disbursed by PT. Erenha Langgeng Karsa. The type of research uses empirical legal research, data sources in the form of primary data and secondary data. The results of the research obtained are a form of legal settlement of the default of the cooperation agreement between PT. Erenha Langgeng Karsa and PT. Tanah Untuk Anak Negeri (Gurindam Property) is by giving a warning and conducting negotiations (deliberations) in a family manner. The factor that caused the default of the cooperation agreement between PT. Erenha Langgeng Karsa and PT. Tanah Untuk Anak Negeri (Gurindam Property) is an economic factor, because PT. Erenha Langgeng Karsa has other bills or arrears to the home material store. So that PT. Erenha Langgeng Karsa prioritizes paying the bill and neglects its obligations to PT. Land for the Nation's Children (Gurindam Property).